Meaning of Umpasa in the Ceremony of Mangongkal Holi in Pangaloan Village: an Anthropolinguistic Study - Lumbanraja, Monika Indriani; Basaria, Ida; Lubis, Rosliana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to describe the meaning and cultural values of umpasa at the Mangongkal Holi ceremony in Pangaloan Village. The problem studied is what are the meanings contained in the Mangongkal Holi ceremony and what cultural values are contained in the Mangongkal Holi ceremony. This research is a type of qualitative descriptive research. The data collection method used is the listening and speaking method. With fishing techniques, skillful involvement, recording and note-taking techniques. Data were analyzed using Robet Sibarani's anthropolinguistic theory (2004: 50), Mansoer Pateda's theory of meaning (2001: 230), and Sibarani's local wisdom theory (2014: 121). The results of the research show that there are two meanings of umpasa in the Mangongkal Holi ceremony, namely the five meanings of advising and the fifteen meanings of expecting something. There are thirteen cultural values found in the umpasa at the Mangongkal Holi ceremony of the Toba Batak community, namely three religious cultural values, two politeness cultural values, three harmony cultural values, two commitment cultural values, two positive thinking cultural values, two cultural values gratitude is three, the cultural value of health is two, the cultural value of gender is two, the cultural value of preservation is two, the cultural value of creativity is one, the cultural value of prosperity is four, the cultural value of mutual cooperation is one and the cultural value of hard work is two.